Konsep Administrasi Pendidikan - Fathimah, Meti; Hasanah, Amalia; Azkiyah, Azkiyah (Lembaga Yasin AlSys, 2024)
This paper explains the concept of educational administration which is a support for achieving educational goals effectively and efficiently. Administration in education that is orderly and organized is needed to improve the ability to manage education for principals and teachers. The purpose of this paper is to explain the meaning, urgency, purpose, function, process and scope of educational administration. The research method used in this research uses the library research method, namely research based on processed manuscripts (manuscript studies), facts and primary and secondary data (supporting data) related to the focus of the research. The results of this study indicate that educational administration is essentially a tool to achieve optimal educational goals. Because the school is a sub-system of the national education system. The educational administration process includes the functions of organizational planning, coordination, communication, supervision, financing supervision, and evaluation. All these functions are very closely related to each other.